Impact of the French National Lockdown on Admissions to 14 Pediatric Intensive Care Units During the 2020 COVID-19 Pandemic–A Retrospective Multicenter Study - Breinig, Sophie; Mortamet, Guillaume; Brossier, David; Amadieu, Romain; Claudet, Isabelle; Javouhey, Etienne; Angoulvant, François; Arnaud, Catherine (Frontiers in Pediatrics, 2021)
Background: After the COVID-19 pandemic reached France in January 2020, a national lockdown including school closures was officially imposed from March 17, 2020, to May 10, 2020. Pediatric intensive care units (PICUs) admit critically ill infants, children and teenagers with severe acute conditions, in particular infectious and traumatic diseases. We hypothesized that PICU admissions would be considerably modified by the lockdown. Aims: The objectives of the study were to describe the type of admissions to French PICUs and to compare the occupation of PICU beds according to local epidemic conditions during the French national lockdown period, compared with the same period the previous year. Methods: We conducted a retrospective multicenter study in 14 French PICUs. All children aged from 7 days to 18 years admitted to one of the 14 participating PICUs over two 3-month period (March 1, 2020, to May 31, 2020 and March 1, 2019, to May 31, 2019) were included. Analysis was based on data extracted from the medicalized information systems program (a national database used in all French hospitals, into which all admissions and their diagnoses are coded for the purpose of calculating hospital funding). Each main diagnosis was reclassified in 13 categories, corresponding to normal PICU admissions. Results: We analyzed a total of 3040 admissions, 1323 during the 2020 study period and 1717 during the same period in 2019. Total admissions decreased by 23% (incidence rate ratio (IRR) 0.77, 95% CI 0.71 to 0.83, p< 0.001), in particular for viral respiratory infections (-36%, IRR 0.64, 95% CI 0.44 to 0.94, p=0.001). Admissions for almost all other diagnostic categories decreased, except intoxications and diabetes which increased, while admissions for cardiac and hemodynamic disorders were stable. Patient age and the sex ratio did not differ between the two periods. Median length of stay in the PICU was longer in 2020 (4 [IQR 2-9] versus 3 [IQR 1-8] days, p = 0.002) in 2019. Mortality remained stable. Conclusions: In this large national study, we showed a decrease in the number of PICU admissions. The most severe patients were still admitted to intensive care and overall mortality remained stable.